Building an information analysis system within a corporate information system for combining and structuring organization data (on the example of a university) - Kopnova, Oxana; Shaporeva, Anna; Iklassova, Kainizhamal; Kushumbayev, Agibay; Tadzhigitov, Askar; Aitymova, Aliya (Eastern-European Journal of Enterprise Technologies, 2022)
Digitalization of all spheres of life has led to the fact that organizations store a large amount of information in various data sources. The process of strategic decision-making may involve an in-depth analysis of data on many items of the organization's production cycle. However, data collection in this case can take weeks. This is quite a long time for prompt decision-making. The object of the study is data stored in the corporate information system of the organization, methods of their analysis for making management decisions. The subject of the study is the automation of work with data within the corporate analytical system, the identification of data analysis patterns, as well as the design of an information analysis system of a university. The presented information analysis system will solve the problem of consolidating disparate data of corporate information systems, as well as operational data of the organization. This is ensured by the creation of a metadatabase and the formation of an information analysis system add-on using PowerBI technologies. The generally accepted design scheme of the information system was modernized demonstrating the place of the metadatabase within the corporate information system of the university. A model of data analysis based on the formation of production rules for building a decision tree on the example of human resources analysis is presented. The results of this study can be useful to analysts, executives and senior managers of large organizations in creating an analysis system for the organization's performance